1999
DOI: 10.1002/(sici)1097-4628(19991227)74:14<3445::aid-app19>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stearic acid treatment of filler particles on the structure and properties of ternary-phase polypropylene composites

Abstract: ABSTRACT:In this study, ternary-phase polypropylene (PP) composites containing an ethylene-octene copolymer (EOR) and calcium carbonate (CaCO 3 ) were investigated. Particular consideration was given to the influence of stearic acid treatment of the filler on the phase morphology and mechanical properties of the composites. In composites containing an uncoated filler, a separate dispersion of the elastomer and filler particles in the PP matrix was observed. The use of filler treated with stearic acid had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 26 publications
5
49
0
Order By: Relevance
“…Two boundary structures may form in such multicomponent materials: the two components, i.e. the elastomer and the filler, can be distributed separately from each other in the polymer matrix [18][19][20], or the elastomer may encapsulate the reinforcement to create embedded structure [11][12][13]21]. The actual structure is determined by the adhesion and shear forces prevailing in the melt during homogenization, the first favors embedding because of thermodynamic reasons, while the second promotes separate dispersion through the shearing of the elastomer layer apart from the filler [22].…”
mentioning
confidence: 99%
“…Two boundary structures may form in such multicomponent materials: the two components, i.e. the elastomer and the filler, can be distributed separately from each other in the polymer matrix [18][19][20], or the elastomer may encapsulate the reinforcement to create embedded structure [11][12][13]21]. The actual structure is determined by the adhesion and shear forces prevailing in the melt during homogenization, the first favors embedding because of thermodynamic reasons, while the second promotes separate dispersion through the shearing of the elastomer layer apart from the filler [22].…”
mentioning
confidence: 99%
“…from each other in the polymer matrix [13][14][15], or the elastomer can encapsulate the reinforcement to create embedded structure [6][7][8]16]. The actual structure is determined by the adhesion and shear forces prevailing in the melt during homogenization, the first favoring embedding because of thermodynamic reasons, while the second separate dispersion through the shearing apart of the elastomer layer from the wood fiber [17].…”
mentioning
confidence: 99%
“…It is not usual to observe an invariable impact resistance in an iPP composition while the mechanical endurance is introduced, and one possible explanation is given by the formation of a new beta crystalline phase [1,2,22] .…”
Section: Waxd (Wide Angle X-ray Diffractometry)mentioning
confidence: 99%
“…Tjong et al [1] analyzed iPP composites having up to 40% of CaCO 3 and concluded that a drop in impact resistance and yield strength with increasing filler content is due to a decrease in the concentration of the tougher polymer matrix, an increase in the amount of the weaker filler/matrix interface, and to the debonding of the filler from the polymer matrix. Premphet & Horanont [2] demonstrated that up to 10% in volume of surface treated CaCO 3 , iPP composites may exhibit higher impact strength, however, concomitantly, a significant reduction in the tensile yield strength. Many researchers [1][2][3][4][5][6][7] have studied the toughening of iPP with CaCO 3 , so the improvement of the impact strength followed by the reduction of yield strength, flexural strength and modulus of the composites are the ordinary outcome.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation